(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Thus, the developed “Scale for assessing the individual risk of bariatric surgery” has sufficient sensitivity and specificity to predict any complications, and can be used in clinical practice to predict and manage the risks of this type of surgical intervention.